2007
DOI: 10.1177/0887302x06296873
|View full text |Cite
|
Sign up to set email alerts
|

Mass Media and Self-Esteem, Body Image, and Eating Disorder Tendencies

Abstract: This study examines whether the level of exposure to mass media is related to self-esteem, body image, and eating disorder tendencies in a nonexperimental setting based on Festinger's social comparison theory. A convenience sample of 114 female college students participated in this study. Significant positive relationships between exposure to fashion or beauty magazines and (a) overall appearance dissatisfaction and (b) eating disorder tendencies were found. No relationship resulted from television exposure. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(53 citation statements)
references
References 77 publications
(123 reference statements)
6
42
1
4
Order By: Relevance
“…Kim and Lennon (2007) found significant positive relationships between women who were exposed to fashion and beauty magazines and body dissatisfaction and eating disorder tendencies. In a similar vein, Thornton and Maurice (1999) found that women exposed to an idealized thin physique expressed decreased self-esteem, insecurity, depression, and other negative effects.…”
Section: Media Effects On Women's Body-imagementioning
confidence: 92%
See 3 more Smart Citations
“…Kim and Lennon (2007) found significant positive relationships between women who were exposed to fashion and beauty magazines and body dissatisfaction and eating disorder tendencies. In a similar vein, Thornton and Maurice (1999) found that women exposed to an idealized thin physique expressed decreased self-esteem, insecurity, depression, and other negative effects.…”
Section: Media Effects On Women's Body-imagementioning
confidence: 92%
“…Researchers who examined the effects of media exposure to the ideal physique found decreased body satisfaction (Harper & Tiggerman, 2008;Groesz, Levine, & Murnen, 2009;Lin & Kulik, 2002), weight-related appearance anxiety (Harper & Tiggerman, 2008), decreased self-esteem (Clay, Vignoles, & Dittmar, 2005), increased mood disturbance (Wegner, Hartman, & Geist, 2000), and increased eating disorder tendencies (e.g., Kim & Lennon, 2007).…”
Section: How Important Are Media Characters To You? Fiementioning
confidence: 99%
See 2 more Smart Citations
“…Embora as utilizadoras da Net saibam da falta de autenticidade das imagens, não deixam de se sentir influenciadas pelos padrões normativos que tendem a associar a feminilidade a um corpo esbelto, ginasticado e jovem (Paraskeva et al, 2015;McKenney & Bigler, 2016). Nalguns casos, as expectativas frustradas sobre os seus corpos pode redundar em trolling, feito pelas próprias mulheres, contra web-celebridades cujos corpos ostentam os padrões idealizados de beleza (Kim & Lennon, 2007). Na sua explicação do termo 'name and shame' (nomear e envergonhar), Jacob Rowbottom (2013) aponta três objectivos desse tipo de acção.…”
Section: Misoginia Online: Disciplinar E Punirunclassified